From the laboratory to the field: heat hardening shields and enhances Mediterranean mussels' physiological performance against global warming - Ioannis Georgoulis; Ioannis A. Giantsis; Basile Michaelidis; Dimitrios K. Papadopoulos; Athanasios Lattos; George Katselis; Konstantinos Feidantsis (Marine Pollution Bulletin, 2025)

Novel insights into the phylogeographic patterns of ascidians fouling Greek mussel cultures - Georgios Geladakis; Charikleia Papaioannou; Vasiliki Kommata; Athanasios Lattos; Dimitrios K. Papadopoulos; Ioannis A. Giantsis; John A. Theodorou; Costas Batargias (Marine Biodiversity, 2025)

Molecular Immune Responses of Ruditapes decussatus to Vibrio Infection at Different Temperatures: Expression of Key Genes and Resilience-Associated Single Nucleotide Polymorphisms - Dimitrios K. Papadopoulos; Ioannis A. Giantsis; Athanasios Lattos; Konstantina Bitchava; Basile Michaelidis (Fishes, 2025)
The impact of pathogenic Vibrio on bivalves is expected to be aggravated by global warming, posing a growing threat to aquaculture. Clam production has been particularly vulnerable, with significant losses attributed to the lack of pathogen-resistant strains. In this study, the mantle cavity of the grooved carpet shell clam Ruditapes decussatus (Linnaeus, 1758) was injected with Vibrio splendidus at 18 °C, 22 °C, and 24 °C and the transcription of the phagelysozyme, Cu-Zn superoxide dismutase (Cu-Zn sod), tumor necrosis factor receptor associated factor 6 (traf6), inhibitor of NF-κB (IκB), and Fas-associated protein with death domain (fadd) genes were assessed during a 20-day period. Additionally, the coding sequences of lysozyme, fadd, and IκB in Ruditapes decussatus were characterized for the first time, and SNPs were identified. Some SNPs showed significantly different distributions between infection-resistant and infection-susceptible individuals. Infected clams experienced increased mortality at elevated temperatures. Lysozyme mRNA was upregulated in infected groups across all temperatures. The sustained increase on day 20, coinciding with elevated traf6 mRNA, suggests a prolonged activation of the immune response. Cu-Zn sod transcription at 18 °C and 22 °C peaked on day 7 and returned to control levels by day 20, indicating an effective immune response, while at 24 °C, infected animals showed a continuously increased transcription. IκΒ and traf6 transcription, reflecting NF-κB pathway activity, varied with temperature and showed transient stimulation at higher temperatures. The pattern of fadd expression indicated a late induction of apoptosis, particularly at 18 °C and 24 °C. Overall, this study illustrates the involvement of five key genes in host–pathogen interactions and identifies potential markers for selection for Vibrio resistance in Ruditapes decussatus. However, given the weak correlation observed, further research is needed on the link between these polymorphisms and pathogen resilience.

Fan Mussel (Pinna nobilis L.) Spat Collection, Monitoring of Early Growth and Conservation Implications by Deploying Conventional Aquaculture Methodology - John A. Theodorou; Efthimios Spinos; Alexis Ramfos; Ioannis E. Tsamadias; Vlasoula Bekiari; Maria Kamilari; Maria-Myrto Ntouni; Dimitrios Tsotsios; Konstantinos Feidantsis; Athanasios Lattos; Ioannis A. Giantsis; Basile Michaelidis (Journal of Marine Science and Engineering, 2024)
Pinna nobilis, endemic to the Mediterranean Sea, has been experiencing a gradual population decline over recent decades due to anthropogenic pressures on its ecosystems. However, since 2016, its populations have suffered significant reductions because of pathological issues affecting the species across all its habitats. Aquaculture techniques to support the limited natural recruitment P. nobilis efforts is examined. Artificial substrates for larval attachments in aquaculture infrastructures promote the survival of the juveniles that is further enhanced through protected pre-growing “nursery” farming conditions. Specific spat collectors were placed in 2 cage-fish farms in SW Amvrakikos Gulf. The harvested spats from were transferred to pre-grow in trays hanged on a long line farm mussel that is acting as a protected “nursery”, avoiding predation and any human accidentally disturbance. The survival and growth of 12 juveniles P. nobilis spat (shell length 38.1 ± 9.2 mm) in captivity (31 October 2023–15 March2023) was investigated. Out of the 12 individuals collected, 3 were examined for the presence of pathogens; only 7 survived, exhibiting enhanced growth (shell length 54.3 ± 11.6 mm) after 134 days in the nursery. The results highlight the significant role of aquaculture techniques in efforts to conserve a threatened species as well as the need for the creation of a protocol to ensure the conservation of P. nobilis.

Molecular characterization of Lernathropus kroyeri from intensive aquaculture and pathophysiology of infested sea bass - Athanasios Lattos; Vasiliki Makri; Dimitrios K. Papadopoulos; Evgenia Gourzioti; Charalampos Pagonis; Ioannis Georgoulis; Dimitrios Karagiannis; John A. Theodorou; Basile Michaelidis; Ioannis A. Giantsis; Konstantinos Feidantsis (Fish & Shellfish Immunology, 2024)

Tropical Shrimp Biofloc Aquaculture within Greenhouses in the Mediterranean: Preconditions, Perspectives, and a Prototype Description - Dimitrios K. Papadopoulos; Maria V. Alvanou; Athanasios Lattos; Kosmas Ouroulis; Ioannis A. Giantsis (Fishes, 2024)
Biofloc technology (BFT) offers an innovative eco-friendly approach that is particularly applicable in shrimp farming. Penaeus vannamei is the most important seafood species in terms of global economic value. Nevertheless, its increasing global demand highlights the necessity for sustainable production of P. vannamei shrimps outside their native range, assuring the avoidance of genetic pollution risk. Towards this direction, the present study focuses on the feasibility of tropical shrimp species aquaculture in indoor systems evaluating BFT application in temperate zones. The achievability of P. vannamei cultivation inside greenhouses in temperate latitudes is thoroughly examined and a representative experimental biofloc setup for P. vannamei within a greenhouse in Northern Greece is demonstrated. Nevertheless, there are two major limitations, related to economy and ecology, namely the energy demand for high seawater temperature and the fact that most reared shrimps are non-indigenous species setting risk for genetic pollution, respectively. To overcome the former, energy-saving measures such as tank and greenhouse insulation in combination with a microclimate chamber construction were implemented to optimize water temperature at minimal cost. Concerning the latter, there is clear evidence that P. vannamei populations cannot be established in the Mediterranean, setting aside any environmental risk. Overall, based on the developed and tested pilot prototype, employment of optimal management practices, innovative manufacturing and clean energy alternatives, and the utilization of ecosystem services could reduce the environmental impact and maximize the profitability of biofloc operations. These actions could probably permit sustainable and economically viable farming of P. vannamei employing BFT within greenhouses in the Mediterranean.

Environmentally Friendly and Efficient Methods for Mitigating the Density of Ascidian Fouling in Mediterranean Mussel Farming - Dimitrios Tsotsios; Dimitrios K. Papadopoulos; Maria V. Alvanou; Ioannis Georgoulis; Athanasios Lattos; Basile Michaelidis; Konstantinos Feidantsis; Ioannis A. Giantsis; John A. Theodorou (Fishes, 2024)
Ascidian biofouling generates significant challenges to bivalve aquaculture. Their rapid spread across almost every available surface leads to increased maintenance costs and reduced yields in shellfish farming. In addition, ascidians may introduce pathogens or toxins, further compromising the health and marketability of bivalve stocks and thereby necessitating strict management strategies to manage these impacts. The aim of this study was the evaluation of different management practices for eliminating ascidian fouling and the identification of the best method for Mytilus galloprovincialis (Lamarck, 1819) aquaculture farms. The effects of different anti-fouling treatments as well as their interactive outcomes were examined by conducting two experiments. Various experimental procedures were applied, including the temporally differential washing of mussels, air exposure and immersion in 50 ppt and 70 ppt salinity solutions, as well as the combination of these applications. All treatments reduced the number of ascidian colonies on mussel socks but at varying proportions. Immersing mussel socks in a 70 ppt salinity solution followed by air exposure for 1 day was the most efficient method and led to a 93% eradication.

The Influence of Water Nitrate Concentration Combined with Elevated Temperature on Rainbow Trout Oncorhynchus mykiss in an Experimental Aquaponic Setup - Dimitrios K. Papadopoulos; Athanasios Lattos; Ioanna Chatzigeorgiou; Aphrodite Tsaballa; Georgios K. Ntinas; Ioannis A. Giantsis (Fishes, 2024)
Intensive recirculating systems are a fast-developing sector of aquaculture. While several warm-water fish have been reared in aquaponics, almost no data are available for cold-water species. The determination of nitrate toxicity thresholds in recirculating aquaculture is crucial. Different pollutants are typically more toxic at elevated temperatures. We investigated the performance of Oncorhynchus mykiss under two different nitrate levels and two temperatures. We applied a 2 × 2 factorial design, where fish (9.78 ± 0.51 g) were exposed to nitrate concentrations of 40 or 110 mg/L NO3− and to temperatures of 17 °C or 21 °C for 20 days. This study focused on understanding the physiological responses of rainbow trout to relatively low nitrate levels under heat stress in order to investigate the feasibility of integrating this species into commercial aquaponics. The growth, condition, and expression of genes involved in metabolism, heat shock, antioxidant, and immune response were assessed in the liver, together with the activities of enzymes related to glucose and fatty acid metabolism. High nitrate levels at 17 °C affected the condition but did not alter growth, leading to increased glycolytic potential and, occasionally, a greater reliance on lipid oxidation. Antioxidant defense was mainly induced due to high nitrates and the similar expression patterns of antioxidant genes observed under high nitrate at both 17 °C and 21 °C. Warm exposure decreased condition and growth, leading to greatly reduced glucokinase transcription, irrespective of the nitrate levels. Exposure to 21 °C and high nitrate led to equivalent growth and condition as well as to a milder inflammatory response combined with metabolic readjustments (enhancement of glycolytic and lipid oxidation pathways) compared to the low nitrates at 21 °C. Based on the results, rearing at a temperature close to 21 °C should be avoided for fingerling growth, while NO3− concentration until 110 mg/L may not have severe impacts on fingerling health and growth at 17 °C. In addition, rainbow trout fingerlings can tolerate a 20-day exposure at 21 °C and NO3− up to 110 mg/L. Additional factors should always be considered, such as specific water quality parameters, for a comprehensive approach to assessing the feasibility of rainbow trout aquaculture in aquaponics.

Antioxidant Defense of Mytilus galloprovincialis Mussels Induced by Marine Heatwaves in Correlation with Marteilia Pathogen Presence - Athanasios Lattos; Dimitrios K. Papadopoulos; Konstantinos Feidantsis; Ioannis A. Giantsis; Ioannis Georgoulis; Dimitrios Karagiannis; Basile Michaelidis (Fishes, 2023)
Background: The effects of climate change negatively affect marine bivalves’ health. Lately, the intensity of marine heatwaves poses serious threats to the aquatic environment setting of high-risk bivalve farming. Since temperature increases can jeopardize bivalves’ immunity response, pathogen infection becomes more evident. Reactive oxygen species (ROS) production, increased during the process of phagocytosis, is confronted by the animals’ antioxidant defense system. However, apart from pathogenic infections, antioxidant defense responses are also induced by seawater temperature increases; Methods: To enlighten the antioxidant status of Mytilus galloprovincialis originating from mortality events enhanced by intense heatwaves in Thermaikos Gulf, northern Greece, along with Marteilia refringens infection, we examined the expression of genes related to antioxidant defense (catalase, CuSOD and mt10) along with the lipid peroxidation levels and activity levels of antioxidant enzymes (catalase, SOD and glutathione reductase); Results: Our results exhibited increased levels of all these biomarkers. This increase was intensified in the Marteilia infected individuals; Conclusions: Our findings shed light on the oxidative and antioxidant status of farmed mussels led to mortality in the context of Marteilia infection. The latter is augmented by the synergistic effect of heatwaves causing a significant increase in oxidative damage and subsequent antioxidant defense.

Mediterranean Aquaculture and Genetic Pollution: A Review Combined with Data from a Fish Farm Evaluating the Ecological Risks of Finfish Escapes - Maria V. Alvanou; Konstantinos Gkagkavouzis; Nikoleta Karaiskou; Konstantinos Feidantsis; Athanasios Lattos; Basile Michaelidis; John A. Theodorou; Costas Batargias; Alexandros Triantafyllidis; Ioannis A. Giantsis (Journal of Marine Science and Engineering, 2023)
Mediterranean finfish aquaculture is mainly represented by the production of the gilthead sea bream (Sparus aurata) and sea bass (Dicentrarchus labrax) growing in marine cage farms. Despite the numerous benefits of fish farming, the ecological risk potentially caused by fish escapes to the wild populations is occasionally high. In the current study, an integrated review of fish escapes is presented regarding S. aurata and D. labrax escapes and their potential effect on the genetic composition of wild populations. The collected data from the literature are combined and discussed along with recorded escapes in a fish farm located in the Aegean Sea, Greece. According to these records, fish escapes present a generally stable rate, ranging between 0 and 2% in each escape event, which occur 5–8 times per year. Although for other farmed fish species worldwide, the ecological risk may be higher, this risk is probably lower in Mediterranean finfish populations, which are characterized by generally low levels of genetic differentiation. Nevertheless, the risk of genetic introgression still exists. Particularly in sea bream and sea bass farming, genetic structure and differentiation in wild populations seem to be unaffected for now. Nevertheless, suitable management measurements would be a useful strategy to avoid future negative effects of fish escapes. These strategies should be focused on further efforts towards recapture program development, reduced escapees’ survival, and proper legislation. Furthermore, more data on escapees’ survival percentage, their migration pathways, and the way these pathways relate to mortality, the type of escape event, and the season of release would be also valuable.

Investigation of the highly endangered Pinna nobilis' mass mortalities: Seasonal and temperature patterns of health status, antioxidant and heat stress responses - Athanasios Lattos; Dimitrios K. Papadopoulos; Ioannis A. Giantsis; Konstantinos Feidantsis; Ioannis Georgoulis; Dimitrios Karagiannis; Francesca Carella; Basile Michaelidis (Marine Environmental Research, 2023)

Impacts of the Establishment of Biofoulants on Greek Aquaculture: Farmers’ Expert Knowledge - Dimitrios Tsotsios; Dimitrios K. Moutopoulos; Athanasios Lattos; Basile Michaelidis; John A. Theodorou (Journal of Marine Science and Engineering, 2023)
Ascidians’ bioaccumulation is frequently responsible for the massive growth of certain species, causing detrimental effects on aquaculture facilities. The goal of this study is to provide, for the first time in the Eastern Mediterranean, information on biofoulant species in Greek mussel farms over a long time scale and to describe the best management strategies that will reduce costs while preventing and controlling these biofoulants. An interview survey was conducted to assess mussel farmers’ expert judgment on non-endemic ascidians as well as their opinions on the magnitude of the invasion’s impacts. The results show that ascidians and, to a lesser extent, sponges exhibited the highest intensities in mussel farm units during the last 20 years, whereas gastropod invasion was limited and observed after 2015. Ascidians exhibited the most significant impact on the final product, whereas sponges showed a moderately negative impact, with reduced amounts of flesh being the most important effect. The cost of farming management only rose with ascidians and sponges and was mostly impacted by damages to maintenance and labor and, to a lesser extent, fuel. All invasive species affected the operational cost of production at a rate of 21–50%, which peaked from July to September. The above problems are increasingly aggravating in cases where farm units undergo production shutdown due to plankton bloom. Preventive management action against the establishment of biofoulants in Greek mussel aquaculture is of paramount importance.

The impact of ascidian biofouling on the farmed Mediterranean mussel Mytilus galloprovincialis physiology and welfare, revealed by stress biomarkers - Dimitrios K. Papadopoulos; Athanasios Lattos; Ioannis A. Giantsis; John A. Theodorou; Basile Michaelidis; Konstantinos Feidantsis (Biofouling, 2023)

The current situation and potential effects of climate change on the microbial load of marine bivalves of the Greek coastlines: an integrative review - Aikaterini Zgouridou; Eirini Tripidaki; Ioannis A. Giantsis; John A. Theodorou; Maria Kalaitzidou; Dionysios E. Raitsos; Athanasios Lattos; Apostolia‐Maria Mavropoulou; Sarantis Sofianos; Dimitrios Karagiannis; Ilias Chaligiannis; Andreas Anestis; et al. (Environmental Microbiology, 2022)
Summary Global warming affects the aquatic ecosystems, accelerating pathogenic microorganisms' and toxic microalgae's growth and spread in marine habitats, and in bivalve molluscs. New parasite invasions are directly linked to oceanic warming. Consumption of pathogen‐infected molluscs impacts human health at different rates, depending, inter alia, on the bacteria taxa. It is therefore necessary to monitor microbiological and chemical contamination of food. Many global cases of poisoning from bivalve consumption can be traced back to Mediterranean regions. This article aims to examine the marine bivalve's infestation rate within the scope of climate change, as well as to evaluate the risk posed by climate change to bivalve welfare and public health. Biological and climatic data literature review was performed from international scientific sources, Greek authorities and State organizations. Focusing on Greek aquaculture and bivalve fisheries, high‐risk index pathogenic parasites and microalgae were observed during summer months, particularly in Thermaikos Gulf. Considering the climate models that predict further temperature increases, it seems that marine organisms will be subjected in the long term to higher temperatures. Due to the positive linkage between temperature and microbial load, the marine areas most affected by this phenomenon are characterized as ‘high risk’ for consumer health.

Pinna nobilis in the Greek seas (NE Mediterranean): on the brink of extinction? - MARIA ZOTOU; PAVLOS GKRANTOUNIS; ELPIDA KARADIMOU; KONSTANTINOS TSIRINTANIS; MARIA SINI; DIMITRIS POURSANIDIS; MARTA AZZOLIN; THANOS DAILIANIS; ELENI KYTINOU; YIANNIS ISSARIS; VASILIS GERAKARIS; MARIA SALOMIDI; et al. (Mediterranean Marine Science, 2020)
The Mediterranean endemic fan mussel Pinna nobilis is suffering an ongoing basin-scale mass mortality event (MME) since 2016. As most Mediterranean populations have collapsed, the species has been declared as Critically Endangered in the IUCN Red List of threatened species. In an effort to track the progress of the MME and provide updated information on the status of the species in the Greek seas, we compiled data collected through dedicated surveys and opportunistic assessments during 2019 and 2020. A total of 14589 fan mussel individuals, of which 81.1% dead, were recorded in 258 site surveys. Of the remaining 2762 live individuals, 256 were juveniles. Two marine areas which still sustain living populations were identified, namely Kalloni Gulf (Lesvos Island), and Laganas Bay (Zakynthos Island). The inner part of Kalloni Gulf appears to maintain the largest surviving population of the species in the eastern Mediterranean, with an abundance estimate of 684000 individuals (95% confidence interval: 322000-1453000). Solitary, potentially resistant, scattered individuals were recorded in several sites. Other previously abundant populations that had been assessed in the past, specifically those of Lake Vouliagmeni (Korinthiakos Gulf), Souda Bay (Crete) and Gera Gulf (Lesvos Island), and which collectively summed up to ~350,000 individuals, have now been wiped out. Our results document the collapse of most P. nobilis populations throughout the Greek seas. The MME has substantially progressed between early 2019 and mid-2020, as indicated by the increase of mortality at sites consecutively monitored multiple times. This work highlights the urgent need for continuous monitoring of surviving populations and calls for the immediate implementation of an effective protection and management strategy that will ensure the persistence of surviving individuals and the production of resistant offspring.